2010
DOI: 10.1590/s0074-02762010000400035
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Schistosoma mansoni infection before and after chemotherapy with two praziquantel doses in a community of Pernambuco, Brazil

Abstract: Praziquantel chemotherapy has been the focus of the Schistosomiasis Control Program in Brazil for the past two decades. Nevertheless, information on the impact of selective chemotherapy against Schistosoma mansoni infection under the conditions confronted by the health teams in endemic municipalities remains scarce. This paper compares the spatial pattern of infection before and after treatment with either a 40 mg/kg or 60 mg/kg dose of praziquantel by determining the intensity of spatial cluster among patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…These values are in general within the usual cure rate ranges (63-95%) of PZQ against S. mansoni reported in different epidemiological settings [4,[26][27][28] . Some previous studies have reported efficacy higher than 85% for PZQ [29][30][31][32][33][34] , while others have reported lower (<63%) efficacy for the drug [13][14][15][16][17][18][19][20][21]35,36] . Such variations might be attributable to differences in the number of treatment, factors related to the host, parasite, and drugs or to the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…These values are in general within the usual cure rate ranges (63-95%) of PZQ against S. mansoni reported in different epidemiological settings [4,[26][27][28] . Some previous studies have reported efficacy higher than 85% for PZQ [29][30][31][32][33][34] , while others have reported lower (<63%) efficacy for the drug [13][14][15][16][17][18][19][20][21]35,36] . Such variations might be attributable to differences in the number of treatment, factors related to the host, parasite, and drugs or to the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important intermediate host for S. mansoni transmission in South America especially Brazil (Paraense and Corrêa, 1989;Melo et al, 2006;Fernandez and Thiengo, 2010). Reports of natural infection of this snail species with S. mansoni were recorded from different parts of Brazil (Malek, 1985;Fernandez and Thiengo, 2010;Galvão et al, 2010;Barboza et al, 2012). Although it is less important for S. mansoni transmission in areas where its distribution overlaps with B. glabrata (Carvalho, 1992), it has been implicated in disease transmission in some Brazilian states, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…All of the Natural snail breeding sites, preferably near schools in the five selected municipalities, were surveyed in July and October 2010, May and November 2011, and October 2012. The geographic coordinates of both the school address and breeding sites of the Biomphalaria snails were captured using a handheld Global Positioning Systems (GPS) receiver (Garmin Etrex Vista) and imported into a Geographic Information System (GIS) for visualization of their spatial distribution (8) .…”
mentioning
confidence: 99%